Exploring the protective effects of aqueous extracts of Ruta Chalepensis Linn. On drug induced seizures in animal models - Bhat, Ramdas; Hemalatha C H; A R Shabaraya (Indian Journal of Pharmacy & Drug Studies, 2023)
Background and Objective: Convulsion is a sudden, involuntary muscle contraction causing rapid and repetitive movements of the body. Ruta Chalepensis Linn. In is a medicinal plant used to treat a wide range of disorders including seizure. But, the anticonvulsant activity of this plant has not been studied in deep. We therefore sought to evaluate the anticonvulsant activity of an aqueous leaf extract of Ruta Chalepensis Linn. On convulsing induced in mice. Method: The anticonvulsant activity of an aqueous leaf extract of Ruta Chalepensis Linn. On convulsing induced in mice, by strychnine nitrate (2.0 mg/kg) and Pentylenetetrazole (PTZ) (80 mg/kg) in mice. Chronic study was conducted using low, medium and high doses of ARC (250, 500 and 750mg/kg respectively). The above-mentioned doses were administered daily once for a period of 7 consecutive days. Aqueous extract (250, 500 and 750 mg/kg), diazepam (10mg/kg intraperitoneally or oral.), and distilled water (10 ml/kg, i.p) were administered before induction of seizures. Results: In strychnine induced convulsion test the onset of seizure was significantly delayed in the animals treated with Ruta Chalepensis Linn leaf aqueous extract at 750mg/kg. In PTZ induced convulsion model the onset of seizure was significantly delayed in the animals treated with Ruta Chalepensis Linn leaf aqueous extract at a dose of 750mg/kg. Conclusion: As a result of foregoing Ruta Chalepensis Linn leaf aqueous extract has considerable diuretic activity at higher doses.